Comparison of Mammography and Ultrasonography in Evaluation of Breast Masses - Nahar, Zebun; Kabir, Md Enamul; Alam, Taharul; Yasmin, Shamoli; Naowar, Maisha (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Breast cancer is the most common cancer and second leading cause of cancer deaths in women. Early detection, efficient and accurate diagnosis can reduce the mortality rate. Objectives: To compare the screening accuracy of mammography (MMG) and ultrasonography (USG) in suspected cases of breast masses. Material and Methods: This cross-sectional analytical study was carried out in the Department of Radiology and Imaging, Combined Military Hospital, Dhaka from June 2016 to July 2017. A total of 100 clinically suspected case of breast masses aged from 20 to 75 years referred for MMG and USG was selected. Each patient underwent USG and MMG followed by a histopathological examination of the biopsy material taken from the lump lesion. Two cases histopathological report was not found. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and diagnostic accuracy of USG and MMG were compared with histopathology as the gold standard. In order to determine the agreement of diagnoses between USG and MMG, consistency analysis was performed using Kappa-statistics. Results: Sensitivity, specificity, PPV, NPV and diagnostic accuracy of USG was 58.8%, 98.4%, 77.8%, 85.0% and 83.6% and for MMG 92.0%, 84.5%, 67.6%, 96.8% and 84.7% respectively. Kappa-statistics shows that the two diagnostic modalities had a test agreement in 39.8% cases to differentiate malignant breast tumour from the benign one (k-value = 0.398, p > 0.05). Conclusion: Two diagnostic modalities USG and MMG had a fair agreement in the differentiation of malignant breast tumour from the benign. Journal of Armed Forces Medical College Bangladesh Vol.13(2) 2017: 22-24